Digital Marketing untuk UMKM: Kunci Optimalisasi Strategi Pemasaran - Ika Puji Saputri; Fathihani Fathihani; Vely Randyantini (BADAN PENERBIT STIEPARI PRESS, 2025)
Bussiness development in the modern era has undergone a significant transformation, shifting from conventional systems to digital-based approaches. Amidst rapid technological advancements and the growing number of internet users in Indonesia, digital marketing has emerged as a strategic solution for expanding market reach efficiently. However, field observations reveal that many Micro, Small, and Medium Enterprises (MSMEs) still face limitations in understanding and implementing digital strategies effectively. Low levels of digital literacy and uneven access to competency certification remain substantial challenges. To address these issues, digital marketing training presents a relevant and timely solution. The main objective of this training is to enhance participants' skills and understanding in conducting digital marketing, which serves as added value for their careers or businesses. The training was delivered through a combination of lectures, practical sessions, and task-based evaluations aligned with the given material. A total of 22 participants—comprising the general public and MSME actors from the Tanjung Duren area, West Jakarta—attended the program. Among them, 82% passed the competency test, while 18% did not meet the required standards. Overall, the training was successfully implemented and proved effective in improving digital marketing competencies among the participants.